Pengaruh Latihan Melempar Keranjang dan Lempar Tangkap terhadap Koordinasi Mata–Tangan Tunagrahita di SLB Paedagogia Surabaya - Riyaldi Rangga Wicaksono; Muhammad Wahyono; Ramadhany Hananto Puriana; Hariadi Hariadi; Rina Nopiana (Jurnal Porkes, 2026)
Children with intellectual disabilities generally experience difficulties with hand-eye coordination due to intellectual dysfunction and delayed motor development. This study aimed to determine the effect of practicing throwing a ball into a basket and throwing and catching a ball against a wall on the hand-eye coordination of students with intellectual disabilities. The study used a quasi-experimental design with a pretest-posttest control group design. The sample consisted of 12 students with mild intellectual disabilities divided into an experimental group (n=6) and a control group (n=6). The experimental group received training for 4 weeks (twice a week, 60 minutes per session), while the control group participated in regular physical education classes. The instrument used was a ball-throwing and catching test with a maximum score of 10. Data analysis utilized paired t-tests and independent t-tests (α=0.05). The results indicated a significant improvement in the experimental group (p=0.001) with a very large effect size (Cohen’s d=2.05), whereas the control group showed no significant improvement (p=0.245). The independent t-test showed a significant difference between the two groups (p=0.004). In conclusion, ball-throwing-into-a-basket and wall-throw-and-catch exercises effectively improve hand-eye coordination in children with mild intellectual disabilities and are recommended for integration into adaptive physical education instruction.